Enhancing the Performance of Piezoelectric Wind Energy Harvester Using Curve-Shaped Attachments on the Bluff Body - Poudel P.; Sharma S.; Ansari M.N.M.; Vaish R.; Kumar R.; Ibrahim S.M.; Thomas P.; Bowen C. (John Wiley and Sons Inc, 2023)
This paper presents a piezoelectric wind energy harvester that operates by a galloping mechanism with different shaped attachments attached to a bluff body. A comparison is made between harvesters that consist of different shaped attachments on a bluff body; these include triangular, circular, square, Y-shaped, and curve-shaped attachments. Simulation of the pressure field and the velocity field variation around the different shaped bluff bodies is performed and it is found that a high pressure difference creates a high lift force on the bluff body with curve-shaped attachments. A theoretical model based on a galloping mechanism is presented, which is verified by experiments. It is observed that the proposed harvester with curve-shaped attachments provides the best performance, where the harvester with a curve-shaped attachments provides the highest voltage and power output compared to the other shaped harvesters examined in this study. This paper provides a new concept for improving the power performance of the piezoelectric wind energy harvesters with modifications made on the bluff body. 2022 The Authors. Global Challenges published by Wiley-VCH GmbH.